Konstruksi Realitas Sosial Pra Dan Pasca Pilkada Di Kab. Wakatobi Dan Buton Tengah Tahun 2024 - Sultrayansa; Wa Ode Hikmawati; Reyhan Dwi Cahyono; Wd Zamira Aulia Putri; Rabiatul Wahda (CV. ITTC INDONESIA, 2025)
This research discusses the construction of social reality that occurred before and after the Regional Head Elections (Pilkada) in Wakatobi Regency and Central Buton Regency using Peter Berger's social construction theory. In the preelection phase, people actively expressed their political views through various platforms, such as social media and public spaces, which created vibrant political dynamics and often tensions. After the election, strong political engagement and collective identities emerge among supporters of candidate pairs (paslon), although differences in expectations of election outcomes can lead to conflict and polarisation. This research highlights how social constructs influence public perceptions, political behaviour and post-election community dynamics.